(untitled) (Research, Society and Development, 2023)
Introduction: The nursing staff plays a fundamental role in the success of organ transplants, being essential in maintaining the potential donor. Therefore, the staff needs to provide high-level care, aiming at excellent patient care. Objectives: To know the perceptions of the nursing staff in relation to the care of the potential donor, to verify the main demands reported by the nursing staff regarding the care of patients with brain death, to describe the sociodemographic profile of the nursing professionals interviewed and the training for care of the potential donor. Methodology: Qualitative, descriptive and exploratory research. Results and Discussion: Ten employees of the nursing staff from the Adult Intensive Care Unit sector of a medium-sized hospital in the Vales Region in Rio Grande do Sul participated in this research. After analyzing the information, four categories emerged: "Perceptions and feelings about the Maintenance of Potential Organ Donors", "Knowledge about the tests applied to potential organ donors", "Training on the topic of Organ Donation, the technical ability and the main questions of the staff”, "The expectations of the staff when participating in the process of maintaining the Potential Donor". Conclusion: It was verified, through the results found, that professionals recognize the importance of humanized, specialized and quality care, they notice weaknesses, they fear and suffer the repercussions in the care process.